2020
DOI: 10.3390/nu12082306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Quercetin and Its Main Methyl, Sulfate, and Glucuronic Acid Conjugates on Cytochrome P450 Enzymes, and on OATP, BCRP and MRP2 Transporters

Abstract: Quercetin is a flavonoid, its glycosides and aglycone are found in significant amounts in several plants and dietary supplements. Because of the high presystemic biotransformation of quercetin, mainly its conjugates appear in circulation. As has been reported in previous studies, quercetin can interact with several proteins of pharmacokinetic importance. However, the interactions of its metabolites with biotransformation enzymes and drug transporters have barely been examined. In this study, the inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 78 publications
(137 reference statements)
0
30
0
Order By: Relevance
“…Functional BCRP has been detected in bEnd3 cerebral endothelial cells and reported to regulate the paracellular tightness [ 8 ]. According to literature data, quercetin and isorhamnetin also exert inhibitory effects on BCRP efflux function and may be candidates for potentiating drug delivery in the brain [ 57 , 58 ]. The detection of isorhamnetin, known to originate from the methylation of quercetin [ 29 ], shows the capacity of cerebral endothelial cells to metabolize quercetin in normoglycemic or hyperglycemic condition, and suggests the possible contribution of isorhamnetin to the biological effects of quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…Functional BCRP has been detected in bEnd3 cerebral endothelial cells and reported to regulate the paracellular tightness [ 8 ]. According to literature data, quercetin and isorhamnetin also exert inhibitory effects on BCRP efflux function and may be candidates for potentiating drug delivery in the brain [ 57 , 58 ]. The detection of isorhamnetin, known to originate from the methylation of quercetin [ 29 ], shows the capacity of cerebral endothelial cells to metabolize quercetin in normoglycemic or hyperglycemic condition, and suggests the possible contribution of isorhamnetin to the biological effects of quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that sulfated derivatives of quercetin and chrysin can inhibit several CYPs in vitro. In particular, quercetin 3′-sulfate has a selective concentration-dependent inhibition activity to CYP2C19 and CYP3A4 up to 30 μM, but the inhibition effect did not exceed 50% and overall was less than that of ticlopidine and ketoconazole (used as positive controls) [ 49 ]. Chrysin 7-sulfate has an IC50 value of 2.7 μM to CYP2C9, which is comparable to that of the positive control sulfaphenazole [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins transport the flavonoid conjugates from the proximal tubular cells to the urine, finally excreting them [46]. The BCRP transporter is not a specific transporter, and quercetin, isorhamnetin, and quercetin 3'-sulfate can also cross the apical membrane via tubular secretion through this transporter [47].…”
Section: Quercetin Metabolites' Luminal Efflux By Tubular Cellsmentioning
confidence: 99%